2021
DOI: 10.3390/plants10071270
|View full text |Cite
|
Sign up to set email alerts
|

ISSR-Based Genetic Diversity Assessment of Genus Jasminum L. (Oleaceae) from Pakistan

Abstract: The genus Jasminum L., of the family Oleaceae, includes many species occurring in the wild, or cultivated worldwide. A preliminary investigation based on inter-simple sequence repeats (ISSR) was performed to assess the genetic diversity among 28 accessions, representing nine species of Jasminum from various regions, representing a range of altitudes in Pakistan. A total of 21 ISSR primers were used, which produced 570 amplified bands of different sizes, with a mean polymorphic band percentage of 98.26%. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…ISSRs segregate mostly as dominant markers following simple Mendelian inheritance. However, they have also been shown to segregate as co-dominant markers in some cases, thus enabling the distinction between homozygotes and heterozygotes [ 21 , 28 , 30 ]. There are some indications that ISSR could be used to identify species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSRs segregate mostly as dominant markers following simple Mendelian inheritance. However, they have also been shown to segregate as co-dominant markers in some cases, thus enabling the distinction between homozygotes and heterozygotes [ 21 , 28 , 30 ]. There are some indications that ISSR could be used to identify species.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al [ 29 ] demonstrated that ISSR was more effective in identifying Alcea species. ISSR was also used by Akhta et al [ 30 ] to identify different species of the genus Jasminum from Pakistan. In addition, ISSR has been employed to investigate genetic diversity in Aconitum species such as A. kongboense L. [ 31 ], A. leucostomum Worosch [ 32 ], and A. carmichaeli [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PIC plays an important role in analyzing the genetic variation [ 32 , 33 ]. The PIC mean values of all primers in this study were greater than 0.25, indicating that the primers tested in this study were effective to demonstrate genetic diversity according to the research results of El-Esawi et al [ 32 ] and Botstein et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Var. total while obtaining the P (rand ≥ data) used the probability in statistical tests (Blyton and Flanagan, 2006;Ennami et al, 2017;Akhtar et al, 2021).…”
Section: Analysis Of Genetic Diversity and Population Structurementioning
confidence: 99%